2014
DOI: 10.1080/02699931.2014.893864
|View full text |Cite
|
Sign up to set email alerts
|

Modulating executive functioning: Trait motivational reactivity and resting HRV

Abstract: This study assessed relationships among individual differences in trait motivational reactivity, executive functioning, and neurovisceral regulation of emotion and attention indexed via resting heart rate variability (rHRV). We derived predictions regarding these relationships according to neurovisceral neural network theory. Because lower rHRV has been suggested as an endophenotype of less adaptive behaviour, low rHRV individuals were predicted to have high aversive and low appetitive trait motivational react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…According to Bailey et al. (), risk avoiders and risk takers are unbalanced motivational groups (high in one system and low in the other system). Bailey et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Bailey et al. (), risk avoiders and risk takers are unbalanced motivational groups (high in one system and low in the other system). Bailey et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bailey et al. () showed that the two unbalanced groups had lower levels of rHRV, indicating more difficulties in cognitive and behavior regulation, when compared to the balanced groups of inactives and coactives that are high or low in both systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations